Was black spruce a good host of the spruce budworm in warmer periods of the Holocene? a long-term reconstruction - Terreaux de Félice, Hugues; Leclerc, Marc-Antoine; Morin, Hubert (Frontiers in Ecology and Evolution, 2025)
Understanding the historical variability in the disturbance dynamics of the most important defoliator in eastern Canada, the spruce budworm (SBW), throughout its range will be paramount in anticipating potential changes associated with current climate change. There is growing concerns that black spruce-dominated forests may become increasingly affected by more frequent and severe outbreaks with warmer spring temperatures. Therefore, in this study, we used lepidopteran scales, a novel paleo-proxy found in lake sediments, to reconstruct periods of large spruce budworm populations (LSBP) along a latitudinal gradient and examined the relationship between large population event frequency relative to geographic location over the course of the Holocene in eastern Canada. The synchronous increase in LSBP event frequency in the four lakes observed around 5500 cal. yr BP culminating in maximum event frequency likely resulted from a combination of the northward migration of balsam fir, and low fire frequency. Although favorable Holocene climate conditions appear to have allowed for the expansion of the spruce budworm’s range into more northerly black spruce-dominated stands, event frequency remained low suggesting that the most suitable area for the SBW appears to be in more southern balsamfir-dominated stands.